Clinicopathological characterisation of duodenal adenocarcinoma with high CD44 variant 9 expression. Issue 7 (December 2015) - Maruyama, Yasuhiro; Uehara, Takeshi; Daikuhara, Seiichi; Kobayashi, Yukihiro; Nakajima, Tomoyuki; Matsumoto, Akihiro; Tanaka, Eiji; Ota, Hiroyoshi
Abstract : Summary: CD44 has been identified as a cancer stem cell (CSC) biomarker in various malignancies. The aim of this study was to elucidate the clinicopathological features of CD44v9 positive cells in duodenal adenocarcinoma (DA). Twenty-nine DA patients were selected from medical archives at our hospital. CD44v9 expression was analysed together with that of MUC2, MUC5AC, and MUC6 by immunohistochemistry. High levels of CD44v9 expression weakly correlated with inflammatory cell infiltration ( r  = 0.431, p  = 0.020) and MUC6 expression ( r  = 0.425, p  = 0.022). Furthermore, double immunofluorescence staining of CD44v9 and Ki-67 or cleaved caspase 3 (CC3) was performed. High- and low-density areas of CD44v9 positive cells were designated as CD44v9 positive and negative areas, respectively. Within CD44v9 positive areas, the level of Ki-67 positivity among CD44v9 positive cells was significantly lower than that of CD44v9 negative cells ( p  = 0.002). Meanwhile, the level of CC3 positivity among CD44v9 positive cells was significantly lower than that of CD44v9 negative cells ( p  < 0.001). CD44v9 expression may be affected by mononuclear cell infiltration and MUC6 expression in DA. CD44v9 positive cells also have a low mitotic activity and resist apoptosis. These characteristics suggest that CD44v9 positive cells possess CSC-like properties in DA.